Peran Orang Tua Dalam Membentuk Karakter Gen Z - Junizar, Junizar; Afni Yan Syah; Siti Nurafifah Qarimah; Husaini (JKA, 2024)
Generation Z, who grew up in the digital age, has unique characteristics and is different from previous generations. As digital natives, Gen Z has the ability to utilize technology but tends to lack social sensitivity. This study aims to explore the role of parents in shaping the character of Gen Z that is balanced between technical competence and social care. Qualitative method with literature study was used in this study. The results suggest that parents should be role models in the healthy and responsible use of technology, as well as encouraging Gen Z to engage in social activities. Collaboration between parents and Gen Z is very important to prepare the next generation who are competent and have good social care